Challenges affecting the implementation of the new business education curriculum in colleges of education in south-east of Nigeria - Chinwe Mikella Nebolisa (CV. Strata Persada Academia, 2024)
This study investigates the challenges affecting the implementation of the new business education curriculum in colleges of education in the South-East region of Nigeria. A survey design was employed to efficiently collect data from 51 participants, including lecturers and students, from selected colleges of education. Self-structured questionnaires distributed via Google Forms accommodated respondents' schedules. To ensure questionnaire validity, input from three professionals in Curriculum Development and Educational Management was sought, yielding Cronbach’s alpha reliability coefficient of 0.89. Data analysis included frequency counts, percentages, mean, standard deviation, and t-tests to assess challenges. The study identified challenges in implementing the new business education curriculum in South-East Nigerian colleges. These include aligning with industry standards, balancing theoretical and practical components, faculty resistance to change, outdated infrastructure, limited funding, and inadequate staffing. Flexibility, practical skills, relevance, adaptation to feedback, digital integration, and budget constraints were highlighted as critical factors. Recommendations include comprehensive training workshops, increased resource provision, policy advocacy, and a culture embracing innovation. Addressing these challenges can enhance the effectiveness of the new business education curriculum, benefiting lecturers, students, and the quality of business education in the South-East of Nigeria.